2007
DOI: 10.1111/j.1365-2141.2007.06896.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of high‐dose methotrexate in central nervous system positive or relapsed lymphoproliferative disease following liver transplant in children

Abstract: SummaryChildhood post-transplant lymphoproliferative disease (PTLD) is a heterogeneous condition in which treatment varies, from the reduction of immunosuppression to moderately intensive chemotherapy. While lowdose chemotherapy/rituximab has been found to be effective, moderately intensive chemotherapy is required for patients who relapse, have classic nonHodgkin lymphoma or have fulminant PTLD. Methotrexate (Mtx) is highly effective in lymphomas and crosses the blood-brain barrier. However, there are no data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 26 publications
2
23
0
2
Order By: Relevance
“…Multiple clinical trials have demonstrated the efficacy of high-dose methotrexate in treatment of primary CNS lymphoma [20]. In addition, chemotherapy with highdose methotrexate has also induced responses in patients with CNS-PTLD after liver and renal transplantation [21,22]. For our patient, concerns about hepatotoxicity and renal toxicity for the high-dose methotrexate, as well as concern about potential bone marrow suppression in a allo-HSCT recipient who was already immunocompromised were reasons not to use high-dose methotrexate as first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical trials have demonstrated the efficacy of high-dose methotrexate in treatment of primary CNS lymphoma [20]. In addition, chemotherapy with highdose methotrexate has also induced responses in patients with CNS-PTLD after liver and renal transplantation [21,22]. For our patient, concerns about hepatotoxicity and renal toxicity for the high-dose methotrexate, as well as concern about potential bone marrow suppression in a allo-HSCT recipient who was already immunocompromised were reasons not to use high-dose methotrexate as first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting biologic observation is that CNS PTLD appears to be more often associated with EBV compared with non-CNS PTLD populations [48,49], although confirmation of this finding is warranted. The optimal therapy for CNS PTLD is not known, but data from several small series suggests that treatment approaches similar to immunocompetent primary CNS lymphoma are important (eg, inclusion of high-dose methotrexate-based therapy) [48,50,51]. We do not advocate RI alone for treatment of primary CNS PTLD in part as this therapeutic maneuver may take several weeks to take effect and these patients are often in need of a more urgent therapeutic response.…”
Section: Cns Ptldmentioning
confidence: 95%
“…67 Hydroxyurea is another less toxic option that can eradicate episomal DNA elements, which may be required for the continued growth of EBV-associated lymphomas. There are several case reports showing the activity of this agent in EBV-associated B-cell lymphoproliferations, particularly with CNS involvement, but these results have not yet been confirmed in prospective trials.…”
Section: Antiviral Agents Antiviral Treatment For Lytic Ebv Infectionmentioning
confidence: 99%